Highest productivity achieved in postrainy (rabi) sorghum: A success story of an award-winning farmer of Maharashtra - Chapke, Rajendra R; Tonapi, Vilas A; Gadakh, S R (Indian Farming, 2022)
This success story proved that the improved sorghum production technologies which were developed by NARS have huge yield potential if these were adopted with careful management of each plant and high input use especially of micro nutrient as practiced by the awarded farmer. Several such high yield potential technologies are available at the research organizations which need to be adopted by the farmers’ in other areas with precise management and passion. They can enhance sorghum productivity by many folds and lead to double and even triple farmers’ income and recurrence of the reduced sorghum area. There is a need to organize regular motivational programmes like crop composition and farmers’ recognition at various levels by the policymakers to promote agriculture and achieve the goal of food, nutrient and income security.